2021
DOI: 10.3390/vaccines9080899
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Protection-Related Type 3 Cell-Mediated Immune Response Elicited by Recombinant Proteins and GM-CSF DNA Vaccine

Abstract: Staphylococcus aureus mastitis remains a major challenge for dairy farming. Here, 24 mice were immunized and divided into four groups: G1: control; G2: Granulocyte Macrophage Colony-Stimulating Factor (GM-CSF) DNA vaccine; G3: F0F1 ATP synthase subunit α (SAS), succinyl-diaminopimelate (SDD), and cysteinyl-tRNA synthetase (CTS) recombinant proteins; and G4: SAS+SDD+CTS plus GM-CSF DNA vaccine. The lymphocyte subpopulations, and the intracellular interleukin-17A (IL-17A) and interferon-γ production in the drain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 63 publications
(110 reference statements)
0
14
0
Order By: Relevance
“…Similar to our findings, [6] reported that the expression of CD44 (i.e., GMFI) was higher in proliferative cells than in nonproliferative cells upon stimulation by PPD in all T cell subsets evaluated in M. bovis-infected cattle. In this regard, it should be noted that dairy cows are constantly exposed to S. aureus, as they are part of the skin microbiota [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our findings, [6] reported that the expression of CD44 (i.e., GMFI) was higher in proliferative cells than in nonproliferative cells upon stimulation by PPD in all T cell subsets evaluated in M. bovis-infected cattle. In this regard, it should be noted that dairy cows are constantly exposed to S. aureus, as they are part of the skin microbiota [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine mastitis is the costliest disease affecting dairy farming and afflicts a high proportion of dairy cows. One of the most common bovine mastitis pathogens is Staphylococcus aureus, which is a notable issue for dairy farming due to its pathogenicity, contagiousness, the likelihood of persistence in the form of intramammary infections, and poor cure rates associated with current antimicrobial therapies; this pathogen has unquestionable importance in veterinary and human medicine [1][2][3]. This bacterium is also known to be part of the skin microbiota [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on proteomic analysis, the current study introduces two affinity purified protein bands isolated from S. aureus extract by affinity column chromatography (CNBr-Sepharose 4B) to be used in the bovine mastitis diagnosis via indirect ELISA. Adoption of proteomics in identification and characterization of S.aureus proteins was previously proved (Santos et al, 2021). Use of CNBr-Sepharose 4B for protein purification of S. aureus is unique and, in most cases, resulted in purified immunogenic components (Forman et al, 1987).…”
Section: Stability Of S Aureus Purified Fractionmentioning
confidence: 99%
“…This observation encouraged us to study their effect on T-cell-mediated immunity which is considered more and more crucial for solid protection against S. aureus infection [ 21 ]. Furthermore, some studies have encouraged the use of a granulocyte-macrophage colony-stimulating factor (GM-CSF) DNA vaccine as a powerful immunoadjuvant [ 22 , 23 ] that could be related to T-cell-derived IL-17 production [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be highlighted that there is growing evidence that T cell immunity, especially T-cell-derived interleukin (IL)-17, plays a pivotal role in protection against S. aureus infections [ 24 , 26 , 27 ]; therefore, a fine-tuned characterization of T cell immunity elicited by the S. aureus proteins above is proposed here. Thus, in the present study, we investigate the immune response induced by three recombinant proteins of S. aureus , EF-G, ENO and PGK in combination with GM-CSF DNA vaccine in mice for future development of use in the cow.…”
Section: Introductionmentioning
confidence: 99%